2014
DOI: 10.1021/jp5094614
|View full text |Cite
|
Sign up to set email alerts
|

Time-, Energy-, and Phase-Resolved Second-Harmonic Generation at Semiconductor Interfaces

Abstract: Interfacial charge transfer is ubiquitous in many chemical and physical processes and can occur on ultrafast time scales of femtoseconds to picoseconds. Probing dynamics on such time scales necessitates the use of ultrafast laser spectroscopies, but signatures of interfacial charge transfer can be overwhelmed by the signal from bulk materials. This problem may be alleviated in second-harmonic generation, which can be specifically sensitive to interfacial charge transfer if other bulk and interfacial contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Regarding the experimental results, the linker system apparently adds an equal unknown background contribution to the SHG signal intensities measured for both PSSs and therefore reduces the apparent NLO contrast. Furthermore, as the phase information 46 is not accessed in our experiment, a negative interference between the chromophore and background contributions cannot be excluded. However, due to the low film thickness we expect only a small phase shift, which does not lead to destructive interference.…”
Section: Calculated Molecular Geometries and Hyperpolarizabilities Pmentioning
confidence: 95%
“…Regarding the experimental results, the linker system apparently adds an equal unknown background contribution to the SHG signal intensities measured for both PSSs and therefore reduces the apparent NLO contrast. Furthermore, as the phase information 46 is not accessed in our experiment, a negative interference between the chromophore and background contributions cannot be excluded. However, due to the low film thickness we expect only a small phase shift, which does not lead to destructive interference.…”
Section: Calculated Molecular Geometries and Hyperpolarizabilities Pmentioning
confidence: 95%
“…Recent studies showed that charge transfer occurs at semiconductor/organic thin film interfaces with timeresolved electric-field induced second harmonic generation (SHG), with the loss of spectral information. [13][14][15][16] Early efforts have also demonstrated the ultrafast relaxation of the surface photo-voltage (SPV) effect on semiconductors by timeresolved photoemission spectroscopy. [17][18][19] The time evolution of the electric field was demonstrated in the surface layer of semiconductors by measuring the kinetic-energy shifts of photoelectrons.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental aspect, second harmonic generation (SHG), has been used to study photoinduced charge separation dynamics in organic semiconductor thin films using the time-resolved spectra technique. Some meaningful results have been obtained, including charge separation from a gradient in excitation density and differential electron/hole mobility in model systems of fullerene (C70) and semiconductor interfaces 28 29 . However, it is reasonable to believe that using quadratic response theory will not considerably affect our qualitative results for photoinduced charge transport efficiency controlled by external electric field.…”
Section: Resultsmentioning
confidence: 99%